Environmental Expenditure Efficiency and its Determinants in Indonesia: A DEA - Tobit Model : JEL Classification: H72, Q58, C24, C61, D24 - Suci Fitriyani; Deky Aji Suseno (Newinera Publisher, 2026)
This study aims to measure the efficiency of environmental expenditure by provincial governments in Indonesia and analyze the socio-economic and structural factors influencing it. Amid global climate challenges and fluctuations in national environmental budgets, evaluating fiscal performance has become essential for sustainable development. This research employs a quantitative approach covering thirty-four provinces over the period from 2020 to 2024. Efficiency is assessed using the Data Envelopment Analysis (DEA) method with an output-oriented Variable Returns to Scale (VRS) approach, where provincial governments are treated as Decision-Making Units (DMUs). The model utilizes environmental expenditure realization as the input, while the recycling rate, protected forest area, renewable energy production, and the Environmental Quality Index serve as outputs. Subsequently, a Tobit regression model is used to examine the determinants of efficiency, including Gross Regional Domestic Product (GRDP), population growth, industrialization level, and the Information and Communication Technology Development Index (ICTDI). The results indicate significant regional variations in efficiency, with only fourteen provinces achieving perfect efficiency scores, while the majority remain below the efficiency threshold. Second-stage analysis reveals that the industrialization level has a positive and significant effect on efficiency, reflecting better governance in developed regions. Conversely, the ICTDI shows a significant negative influence, indicating suboptimal technology integration in budget management. Economic capacity and population growth do not statistically explain efficiency variations. These findings suggest that the government should transition from an expenditure-based approach to performance-based budgeting by strengthening digital oversight systems and promoting green industrialization to ensure sustainable environmental quality improvement in Indonesia.